Notes on Carex (Cyperaceae) from China (II): a taxonomic revision of sect. Radicales (Kük.) Nelmes - Jin, Xiao-Feng; Cen, Jia-Meng; Hahn, Marlene; Lu, Yi-Fei; He, Jin-Jing (Phytotaxa, 2015)
Section Radicales (Kük.) Nelmes comprises nearly 15 species in Carex subg. Carex (Cyperaceae) and is mainly distributed in the Pan-Himalaya region, with a few species extending to the Guangxi and Hainan provinces of China and Burma. A taxonomic revision of sect. Radicales in China is proposed and 12 species with two varieties are recognized. Carex pseudomitrata X. F. Jin & Cen is described as a new species and C. caudispicata var. longiutriculata X. F. Jin is described as a new variety. Carex anningensis is reduced to synonym of C. caudispicata, and C. chuiana to C. radicalis. Carex funhuangshanica and C. speciosa subsp. dilatata are respectively reduced to synonyms of C. speciosa and C. speciosa var. courtallensis.